FINANCIAL CAPACITIES OF THE LOCAL BUDGET IN THE DEVELOPMENT OF REGIONS - Abdurazzakov Bakhodir (Western European Studies, 2026)
The article studies the problem of the financial capabilities of the local budget in the development of regions in connection with the declaration by the President of 2026 as the “Year of Neighborhood Development and Society Upliftment”. The structure of the local budget, sources of income entering it (local taxes, fees, transfers, etc.) are considered in detail. The impact of the local budget on socio-economic development, ways to strengthen and increase its effectiveness, and existing shortcomings (for example, the lack of circulation of bills) are also substantiated. The article also presents proposals for the distribution of budget expenditures and increasing local financial independence. The results of the study have practical value in improving local budget policy and strengthening financial support for the sustainable development of regions.
Keywords: local budget; budget capabilities; neighborhood development